Multiple Intelligences Based Learning: Concepts and Applications in Elementary Schools (Case study in Unggulan Permatajingga Elementary School Malang) - Jamal Abdul Naser, M. Saunan Al Faruq (International Journal of Advanced Science and Technology, 2020)
Multiple Intelligences (MI) is a learning concept that is based on diversity of intelligences. This research using the qualitative method i.e. case study in Permatajingga Primary School. The results showed that the school’s commitment to facilitate the development of students according to their intelligences potential was used as the foundation of learning. The primary school in this study decided to apply the concept of MI-based-learning since the beginning of the founding of the school. The concept is then used as a basis for programming and managing learning in schools.